GAMBARAN KEJADIAN VITILIGO DI RSUD DR. RM DJOELHAM KOTA BINJAI PERIODE 1 JANUARI 2015 - 1 SEPTEMBER 2019 - HERVINA .; YENITA . (JURNAL ILMIAH MAKSITEK, 2021)
Vitiligo is a pigmentation disorder, characterized by hypopigmented macules caused by chronic and progressive loss ofepidermal melanocyte function. The cause of vitiligo is not yet known with certainty the cause. According to some studies theincidence of vitiligo is more frequent in women, aged 20-40 years and in students. This study uses a descriptive method witha retrospective approach. Data were obtained from the medical records of vitiligo patients in the period January 1 2015 -September 1 2019. In January 2015 - September 2019 in Dr. RM Djoelham Binjai City found the highest incidence of vitiligooccurred in women as many as 35 people (63.6%), the incidence of age was more prevalent at the age of 11-20 years asmany as 17 people (30.9%), the incidence based on more work many occur in students as many as 20 people (36.4%).Based on the results of a study describing the incidence of vitiligo in the Skin and Sex Health clinic Dr. RM Djoelham KotaBinjai mostly occurs in women, the incidence of age mostly occurs at the age of 11-20 years and the incidence of work ismore common in students.